Initiation of genomics-assisted breeding in Virginia-type peanuts through the generation of a de novo reference genome and informative markers - Newman, Cassondra S.; Andres, Ryan J.; Youngblood, Ramey C.; Campbell, Jacqueline D.; Simpson, Sheron A.; Cannon, Steven B.; Scheffler, Brian E.; Oakley, Andrew T.; Hulse-Kemp, Amanda M.; Dunne, Jeffrey C. (Frontiers in Plant Science, 2023)
Introduction Virginia-type peanut, Arachis hypogaea subsp. hypogaea, is the second largest market class of peanut cultivated in the United States. It is mainly used for large-seeded, in-shell products. Historically, Virginia-type peanut cultivars were developed through long-term recurrent phenotypic selection and wild species introgression projects. Contemporary genomic technologies represent a unique opportunity to revolutionize the traditional breeding pipeline. While there are genomic tools available for wild and cultivated peanuts, none are tailored specifically to applied Virginia-type cultivar development programs. Methods and respective results Here, the first Virginia-type peanut reference genome, “Bailey II”, was assembled. It has improved contiguity and reduced instances of manual curation in chromosome arms. Whole-genome sequencing and marker discovery was conducted on 66 peanut lines which resulted in 1.15 million markers. The high marker resolution achieved allowed 34 unique wild species introgression blocks to be cataloged in the A. hypogaea genome, some of which are known to confer resistance to one or more pathogens. To enable marker-assisted selection of the blocks, 111 PCR Allele Competitive Extension assays were designed. Forty thousand high quality markers were selected from the full set that are suitable for mid-density genotyping for genomic selection. Genomic data from representative advanced Virginia-type peanut lines suggests this is an appropriate base population for genomic selection. Discussion The findings and tools produced in this research will allow for rapid genetic gain in the Virginia-type peanut population. Genomics-assisted breeding will allow swift response to changing biotic and abiotic threats, and ultimately the development of superior cultivars for public use and consumption.